Financial Literacy of Indonesian Migrant Workers in Malaysia: Policy Evidence from the National Financial Literacy Strategy - Annisa Nur Salam; Achmad Rizal; Danial Muhammad Wirdyansyah (Diponegoro Journal of Economics, 2026)
Financial literacy is a key policy instrument for strengthening financial inclusion, economic resilience, and social stability. In Malaysia, this objective is supported through the National Financial Literacy Strategy, which emphasizes inclusive financial education and responsible financial behavior, particularly among vulnerable populations. Indonesian migrant workers constitute a substantial segment of Malaysia’s labor force; however, limited financial literacy continues to hinder their participation in formal financial services and efficient remittance management. This study examines the determinants of financial literacy among Indonesian migrant workers in Malaysia, focusing on financial attitude, financial behavior, and financial socialization. Using a quantitative approach, data were collected from 205 respondents through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The study contributes to the literature in three ways: (1) developing a migrant-worker-specific model of financial literacy in a cross-border labor context; (2) incorporating financial socialization as a key determinant, emphasizing the influence of family, peers, and workplace learning; and (3) extending the policy relevance of financial literacy research by linking behavioral factors to broader financial inclusion outcomes. The findings reveal that financial attitude, financial behavior, and financial socialization have positive and statistically significant effects on financial literacy. These results support the objectives of Malaysia’s National Financial Literacy Strategy and offer practical implications for policymakers and financial regulators, particularly Bank Negara Malaysia. The study highlights the need for targeted financial literacy programs delivered through formal financial institutions, remittance service providers, and employer-based initiatives to improve financial capability and promote sustainable financial inclusion among migrant workers.